A Signature of Five Long Non-Coding RNAs for Predicting the Prognosis of Alzheimer's Disease Based on Competing Endogenous RNA Networks - Huaying, Cai; Xing, Jin; Luya, Jin; Linhui, Ni; Di, Sun; Xianjun, Ding (Frontiers in Aging Neuroscience, 2021)
Long non-coding RNAs (lncRNAs) play important roles in the pathogenesis of Alzheimer's disease (AD). However, the functions and regulatory mechanisms of lncRNA are largely unclear. Herein, we obtained 3158 lncRNAs by microarray re-annotation. A global network of ceRNAs was developed for AD and normal samples based on the gene expressions profiles. A total of 255 AD-deficient mRNA-lncRNAs were identified by expression correlation analysis. Genes in the dysregulated ceRNAs were found to be mainly enriched in transcription factors and miRNAs. Analysis of the disordered miRNA in the lncRNA-mRNA network revealed that 40 pairs of lncRNA shared more than 1 disordered miRNA. Among them, 9 lncRNAs were closely associated with AD, Parkinson's and other neurodegenerative diseases. Of note, 5 lncRNAs were found to be potential biomarkers for AD. qRT-PCR assay revealed that PART1 was downregulated, while SNHG14 was upregulated in AD serum samples when compared to normal samples. This study elucidates on the role of lncRNAs in the pathogenesis of AD, and presents new lncRNAs that can be exploited to design diagnostic and therapeutic agents for AD.